Linking Scholarship and Practice: Narrative and Identity in Science - Neeley, Liz; Barker, Erin; Bayer, Skylar R.; Maktoufi, Reyhaneh; Wu, Katherine J.; Zaringhalam, Maryam (Frontiers in Communication, 2020)
In recent years, science communicators have enthusiastically embraced storytelling as a means of dramatizing the process of science and humanizing the scientists who conduct it. Compared to evidence-based argumentation, narratives do tend to be more engaging, more comprehensible, more believable, and more persuasive to non-specialist audiences. However, the gaps between research and practice in this field are considerable, in part because both comprise many distinct areas of expertise. Here, we draw on our experience as a professional storytelling organization and seek to narrow some of these gaps by linking the scholarship to our practice, and to encourage engagement with scholars about future directions in the field. This perspective article intends to synthesize theory and practice to address two major questions: What is the impact of stories on audiences? What is the impact of stories on their tellers? We consider both questions in the knowledge that science and science communication are only beginning to address the historic and ongoing underrepresentation of stories from many racial, ethnic, cultural, religious, gender, and socioeconomic groups. We focus on how stories influence social stereotypes about scientists, as well as identity and belonging within science, and conclude with the link between narrative identity and mental health and well-being.